2009
DOI: 10.1186/2047-783x-14-s4-265
|View full text |Cite
|
Sign up to set email alerts
|

Co-trimoxazole and prevention of relapses of PR3-ANCA positive vasculitis with pulmonary involvement

Abstract: BackgroundBacterial and viral respiratory tract infections may trigger relapses in patients with PR3-positive vasculitis. Data have suggested that treatment with co-trimoxazole may be beneficial, because this antibiotic could act by eliminating the offending microbe and thereby stopping the initiating stimulus.Goal and methodsProspective, randomized, placebocontrolled study of the efficacy of co-trimoxazole given 960 mg thrice weekly for 18 months in preventing relapses in patients with Wegener's granulomatosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 17 publications
(18 reference statements)
1
45
0
2
Order By: Relevance
“…This is much higher than in the general population. S. aureus carriers are at higher risk of relapse of GPA than non-carriers, and treatment with trimethoprim-sulfamethoxazole resulted in significant reduction of relapse rate [76][77][78]. Multiple mechanisms may contribute to the increased risk of relapse conveyed by S. aureus.…”
Section: Infectious Triggersmentioning
confidence: 94%
“…This is much higher than in the general population. S. aureus carriers are at higher risk of relapse of GPA than non-carriers, and treatment with trimethoprim-sulfamethoxazole resulted in significant reduction of relapse rate [76][77][78]. Multiple mechanisms may contribute to the increased risk of relapse conveyed by S. aureus.…”
Section: Infectious Triggersmentioning
confidence: 94%
“…A second report [48] from the same group also concluded inefficacy of co-trimoxazole prophylaxis for maintaining remission in generalized Wegener's granulomatosis, although the drug could be effective in the initial phase, that is locoregional Wegener's granulomatosis. A more recent controlled study [49] on the prophylactic use of co-trimoxazole (960 mg thrice weekly) in maintaining remission in 31 patients with Wegener's granulomatosis showed a small but significant effect of co-trimoxazole: 75% of patients (n ¼ 16) in the co-trimoxazole group vs. 55% in the placebo group (n ¼ 15) maintained remission during the 18 months' study period. This study also confirmed risk factors for relapse: a positive test for PR3-ANCA at remission, chronic nasal crusting, and carriage of S. aureus.…”
Section: Antineutrophil Cytoplasmic Autoantibodyassociated Vasculitismentioning
confidence: 95%
“…Data have suggested that treatment with cotrimoxazole may be beneficial, because this antibiotic could act by eliminating the offending microbe and thereby stopping the initiating stimulus in these patients. Treatment with cotrimoxazole has been shown to reduce the incidence of relapses in patients with WG/GPA in remission in previous studies [142,143], and should be considered in cases of persistent endonasal activity of WG/GPA, together with S. aureus carriage [144]. Cotrimoxazole was also recommended by both EULAR [128] and the British Society for Rheumatology (BSR) and British Health Professionals in Rheumatology (BPHR) guidelines [145] as prophylaxis against Pneumocystis jerovicii infection in patients with WG/GPA.…”
Section: Maintenance Therapymentioning
confidence: 96%